Modelling of multiphase flow containing ionic liquids in a stirred tank reactor - Dong, Jie (2017)
Stirred tanks are widely used in the chemical reactions and the mixing operations for process industries to enable high product quality and process efficiency. Despite there being a large body of studies on the hydrodynamics of water in the stirred tanks, the understandings of the hydrodynamics of the ionic liquids in the stirred tanks are still very limited. In this study, Computational Fluid Dynamics (CFD) modelling is used to investigate the detailed flow characteristics of the single and multiphase ionic liquid flows in the stirred tanks which are experimentally validated using Particle Image Velocimetry (PIV).